The Value of Administrative Staff for Internationalization - Brandenburg, Uwe (International Higher Education, 2016)
Administrative staff, including those working for international offices, housing officials, and many others play a key role in international higher education. Without their professionalism and involvement, virtually all aspects of university internationalization would fail.